A PRENYLATED FLAVONE FROM THE HEARTWOOD OF Artocarpus scortechinii King (Moraceae) - Aliefman Hakim (Indonesian Journal of Chemistry, 2009)
Two prenylated flavones have been successfully isolated from the methanol extract of the heartwood Artocarpus scortechinii King. They were determined as artelastisin and artelastin. It has been reported that artelastisin and artelastin were obtained from Artocarpus elasticus. The cytotoxicity toward cell murine leukemia P-388 showed that artelastisin is active with IC50 3.0 µg/mL. In addition, artelastin is inactive with IC50 5.75 µg/mL. The structures of isolated compounds were determined based on spectroscopy data including UV, IR, 1H and 13C-NMR. These compounds are reported for the fist time from this plant.